Case report Ultrasound findings in cutaneous sarcoidosis: report of a case - Dybiec, Ewa; Pietrzak, Aldona; Bartosińska, Joanna; Kieszko, Robert; Kanitakis, Jean (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
The diagnosis of cutaneous sarcoidosis relies mainly on the patient’s history, presence of characteristic skin lesions and histological examination that shows a granulomatous, non-necrotizing dermal infiltration. The aim of the study was to assess the ultrasonographic features of cutaneous lesions of sarcoidosis before and after treatment. A 38-year-old woman with systemic sarcoidosis and specific cutaneous lesions was treated with systemic steroids followed by hydroxychloroquine. Ultrasonographic examination of the cutaneous sarcoidosis lesions was performed with a Philips iU 22 and Siemens Acuson S 2000 device, with the use of linear 15 MHz and 17 MHz transducers. Histological examination of skin lesions showed characteristic, naked, non-necrotizing granulomas in the upper dermis. Ultrasound examination revealed well-demarcated, hypoechogenic changes. Power-Doppler scan revealed increased vascularity within the lesions and the surrounding tissue. Clinical improvement of the skin lesions was confirmed by ultrasound examination, which showed a decrease in their size and normalization of dermal echogenicity and vascularity. Ultrasound examination can show cutaneous sarcoidosis lesions and their regression after appropriate treatment.